2018
DOI: 10.3329/bsmmuj.v11i3.37701
|View full text |Cite
|
Sign up to set email alerts
|

Study on clinical features and factors associated with thickness of chronic subdural hematoma in adult

Abstract: <p class="Abstract">Patients with chronic subdural hematoma encounter certain difficulties in diagnosis, especially in elderly, due to the characteristically non-specific symptoms and signs. Early diagnosis and proper operative treatment, on the other hand, results in complete recovery in most of the cases. In this study, the clinical features and factors of 31 patients with chronic subdural hematoma, associated with the thickness of chronic subdural hematoma were analyzed. The mean age was 62 ± 13.9 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Studies vary in the reported incidence of papilledema in patients with CSDH. It has been reported that the incidence of papilledema in patients with CSDH in the studies conducted before the nineteen nineties ranged from 20% to 75% [11][12][13][14][15][16], and in more recent studies was as low as 0.4%-2% [17,18]. Over the two recent decades, there have been anecdotal reports on bilateral papilledema in patients with CSDH [19,20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies vary in the reported incidence of papilledema in patients with CSDH. It has been reported that the incidence of papilledema in patients with CSDH in the studies conducted before the nineteen nineties ranged from 20% to 75% [11][12][13][14][15][16], and in more recent studies was as low as 0.4%-2% [17,18]. Over the two recent decades, there have been anecdotal reports on bilateral papilledema in patients with CSDH [19,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…The difference in age structure of the study sample and early diagnosis of CSDH are likely to explain the difference in the reported incidence of papilledema in patients with CSDH between studies. It has been reported that papilledema is seen more often in children and young adults [14,22]. Consequently, it should be also taken into account that, with aging of the general population, there will be a shift in the peak incidence of CSDH from the younger age group to the older age group.…”
Section: Discussionmentioning
confidence: 99%